Plasma local diagnostics by polarimetric method. (1st May 2023) - Oganesyan, Koryun B; Dzierżęga, Krzysztof; Gevorgyan, Ashot H; Hnatic, Michal; Kopcansky, Peter
Abstract: We study the polarization plane rotation of weak probe signal in the field of strong electromagnetic waves in the presence of an external magnetic field of plasma, the polarization plane stimulated rotation angle of the probe signal in the intense laser field and in plasma is calculated. The estimates of the residual gas local density in a cesium plasma based on the effects of Faraday, Cotton–Mouton and stimulated rotation of the probe signal in the intense laser field have been found. It is shown, that the rotation angle in the cesium plasma medium has a complex structure.